HUBUNGAN KONTROL DIRI DENGAN KECENDERUNGAN FEAR OF MISSING OUT PADA REMAJA PENGGUNA AKTIF MEDIA SOSIAL TIKTOK - Liesbeth Marnes Pattinama; Wahyuni Kristinawati (Journal of Innovation Research and Knowledge, 2024)
Fear of missing out is a feeling of anxiety, worry and fear that a person experiences when they feel left behind by other people's experiences which they consider more valuable than their own. One of the factors that influences the fear of missing out is the ability to control oneself. The aim of this research was to determine the relationship between self-control carried out on 101 teenagers, aged 15-18 years who actively used Tiktok social media, with a correlational quantitative approach. Data was obtained using a self-control scale modified by (Ghufron & Rini, 2010), namely: behavioral control, cognitive control, and decisional control and a fear of missing out (FOMO) scale based on aspects proposed by Przybylski, Murayama, DeHaan and Gladwell (2013). The results of the correlational test were carried out using Product Moment correlation and obtained a correlation coefficient of -0.380 with a sig value. = 0.000 (p<0.01), which means there is a negative relationship between self-control and the tendency to fear of missing out in teenagers who are active users of Tiktok social media.